Protective effects of Boswellia and Curcuma extract on oxaliplatin-induced neuropathy via modulation of NF-κB signaling - Sakshi Mahajan; Varun Sureja; Dharmeshkumar Kheni; Vishal Dubey; Kiran Bhupathiraju; Venkata KrishnaRaju Alluri; Anuradha Majumdar (Toxicology Reports, 2024)
Oxaliplatin is a third-generation anticancer agent with better efficacy, lower toxicity, and a broad spectrum of antineoplastic activity. Its use is frequently associated with chronic oxaliplatin-induced neuropathy (OIN), a cumulative phenomenon manifesting as loss of sensation, paresthesia, dysesthesia, and irresolvable fluctuations in proprioception that greatly affect the patients’ quality of life. The inevitable nature and high incidence of OIN, along with the absence of efficacious preventive agents, necessitate the development of effective and reliable protective options for limiting OIN while maintaining anticancer activity. The pathogenesis of chronic OIN involves neuroinflammation and oxidative stress. This study aimed to explore the neuroprotective effects of Boswellia serrata and Curcuma longa via modulation of nuclear factor-kappa B (NF-κB) signaling. Behavioral tests were conducted to assess cold allodynia, heat hyperalgesia, mechanical allodynia, mechanical hyperalgesia, and slowed nerve conduction velocity associated with chronic oxaliplatin administration. The modulation of NF-κB signaling and the subsequent activation of cytokines were evaluated through quantitative analysis of inflammatory cytokines in sciatic nerve homogenates. Additional assessments included oxidative stress parameters, serum neuronal biomarkers, and examination of sciatic nerve cross-sections. The findings indicate improvements in behavioral and biochemical parameters, as well as nerve histology, with the combined extract of Boswellia serrata and Curcuma longa at doses of 50 mg/kg and 75 mg/kg. Thus, this study presents evidence for the protective potential of the combined extract of Boswellia serrata and Curcuma longa in OIN through modulation of NF-κB signaling.